Специфика колымского юмора - Gorbaczewskij, Czesław (Acta Polono-Ruthenica, 2018)
The article is devoted to the problem of „Kolyma humour”. This term is consider by formers Kolyma political prisoners such as Varlam Shalamov, Daniil Alin, Georgiy Demidov, Zalman Roomer, Wernon Kress, Juriy Dombrowskiy etc. „Kolyma humour” as definition sounded quite absurdly with reference to slavish condition of existence huge quantity deprived elementary civil rights people. Through „Kolyma humour” everyone can see the extremely cruel attitude so called „friends of people” to „enemies of people”. As a result: only human with fatal deformed conscio- usness has ability for understanding such kind of non-human humour, called „Kolyma humour”.